The Greece Building, New York World's Fair (Tichnor Brothers, Inc)
The story of Greece and the glory of her ancient culture is portrayed in this Exhibit thru the medium of paintings and dioramas. Throughout the years Greece has been world-famed for her products and many of them are here displayed including wines, fruits, tobacco, fine silks and hand woven oriental rugs, ceramics, chemicals and minerals.